DESCRIPTION OF VALUES IN THE WORKPLACE, INTERPERSONAL RELATIONSHIPS, WORK ORGANIZATION, AND WORK CONTENT IN EMPLOYEES OF HOTEL X MAKASSAR CITY - Fatmawaty Mallapiang; Azriful Azriful; Triana Andika Putri (Homes Journal = Hospital Management Studies Journal, 2021)
Background: To improve safety and health in the work environment, prevention needs to be taken with attention to psychosocial in the workplace. This is because the workplace is a source of psychosocial risk and also an ideal place to deal with these risks in protecting the health and well-being of workers.Objective: This research aims to know the picture of values in the workplace,interpersonal and leadership relationships, work for an organization, and work content in the workplace at the employees of Hotel X Makassar City.Method: The type of research used is quantitative descriptive. Sampling was conducted by the Total Sampling method of 56 respondents.Result: The results of the study found that 19.6% of categories lack values in the workplace, 12.5% of employees have fewer interpersonal and leadership relationships and the organization of work and work content is 12.5% less.Conclusion: The conclusion in this study is that values in the workplace have not been fairly distributed, the lack of social support from colleagues in aspects of interpersonal relationships and leadership, work organization, and worker work content is still lacking in contributing to the organization in the workplace. Therefore, it is expected that the company adjusts between working capacity and workload